Opini Publik Mengenai Piala Dunia Qatar - Syilfa Fakhira; Dita Isnata; Yasyfa Fitri; Maylanny Christin (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this study is to find out how the 2022 World Cup audience thinks about the pros and cons of anti-LGBT at the World Cup in Qatar. The research method uses qualitative research methods with a descriptive approach. The data collection technique used was in-depth interviews with international students watching the 2022 World Cup. The main theory in this research is public opinion theory. The results of this study indicate that the audience's opinion about the Pros and Cons of LGBT, basically the State of Qatar adheres to religious principles (anti-LGBT) which is very contrary to the principles of most participating countries in the World Cup which tend to be liberal & prioritize human rights. Qatar realizes that World Cup participants have various elements, one of which is multiculturalism. However, the country of Qatar continues to use its rules where Qatar is the host of the 2022 World Cup, therefore it must follow the rules that apply in the country of Qatar. The conclusions of this study show that there are many student perspectives that are against the LGBT events at the World Cup that took place in Qatar Keywords: LGBT, Public Opinion, Pros and Cons, Qatar, Qualitative, World Cup